The design and stress analysis of an integral land rover structure - Tidbury, G. H. (College of Aeronautics, 1968)
This report gives in detail the calculation of the distribution of forces in an integral structure by the matrix force method. The design of a full scale structure to test the theoretical results is described in an Appendix but test results will be given in a separate report. The method of analysis is suitable for a small, first generation digital computer and would now be superceded by 'automatic' programs on large computers.